ANALISIS STRATEGI PT. BURSA EFEK INDONESIA - ABRIZEN JUSTA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
The object of research is PT. Indonesia Stock Exchange Representative Office Padang. The data collection technique using semi structured interviews and analysis of document and material as well as questionnaires given to three employees of the Head Office, Staff Trainer and Administrative Staff. The object of research is PT. Indonesia Stock Exchange Representative Office Padang. Strategy formulation using matrix EFE, IFE, SWOT, IE, and QSPM. Acquisition of strategic alternatives is obtained from the SWOT matrix and Matrix IE, to choose the best strategy with Quantitative Strategic Planning Matrix. Based on the analysis IFE and EFE matrix, it is known that the main strength of PT. Indonesia Stock Exchange Representative Office of Padang is the number of educational programs have to offer while its main drawback is the lack of promotional activity for advertising in print or digital. The main opportunities for PT. Indonesia Stock Exchange Representative Office of Padang is the huge barriers to entry of new entrants, while the major threats facing is the lack of human resources in the area, the majority of the best people prefer to wander. IE matrix shows that PT. Indonesia Stock Exchange Representative Office of Padang is in quadrant 1 (one) which is to be on growing conditions and build. Based on the obtained QSPM alternative appropriate marketing strategies in this study is the product development strategy.